Risk factors for macrophage activation syndrome in systemic juvenile idiopathic arthritis: a systematic review and meta-analysis - Li, Shihao; Wu, Xin; Jing, Shuolan; Yang, Xianglin; Zhang, Yuqing; Dong, Liqun (Frontiers in Pediatrics, 2025)
BackgroundMacrophage activation syndrome (MAS) is among the most life-threatening complications of systemic juvenile idiopathic arthritis (sJIA). Early identification of risk factors is critical for reducing mortality. However, existing evidence is markedly heterogeneous and lacks quantified, comparable, and clinically translatable conclusions.MethodsWe systematically searched PubMed, Web of Science, EMBASE, and Chinese databases, including China national knowledge infrastructure (CNKI), Wanfang, VIP, and Chinese biomedical literature database (CBM), from inception to 1 July 2025, for case–control studies investigating risk factors for MAS in sJIA. Two investigators independently screened studies, extracted data, and assessed study quality. Meta-analyses were performed using RevMan 5.3 and Stata 16.0.ResultA total of 10 studies involving 1,936 patients were included, comprising 643 cases and 1,293 controls. Meta-analysis showed that central nervous system (CNS) involvement, hypofibrinogenemia, markedly elevated ferritin levels, and leukopenia were significantly associated with MAS in sJIA, with odds ratios (95% confidence intervals) of 4.30 (2.13–8.65), 4.03 (2.87–5.65), 8.28 (5.66–12.10), and 5.98 (2.80–12.75), respectively.ConclusionCNS involvement, hypofibrinogenemia, hyperferritinemia, and leukopenia are core risk factors for MAS in patients with sJIA.Systematic Review RegistrationPROSPERO CRD420251108082.